A multi-agent system to manage users and spaces in a adaptive environment system - Oliveira, Pedro Filipe (2020)
This paper, deals with the actual problem of manage user preferences and local speci cations on an IoT adaptive system, namely using a multi agent system to achieve a Smart Environment System. On a new era of interaction between persons and physical spaces, users want those spaces smartly adapt to their preferences in a transparent way. To achieve that, new approaches are needed. In this project we develop a multi agent system architecture with di erent layers to achieve a solution that entails all the proposed objectives.